Ulnar Shortening Osteotomy for Ulnar-Sided Wrist Pain - Tatebe, Masahiro; Nishizuka, Takanobu; Hirata, Hitoshi; Nakamura, Ryogo (Journal of Wrist Surgery, 2014)
Background The purpose of ulnar shortening osteotomy is literally to shorten the ulna. It can tighten the triangular fibrocartilage complex (TFCC), ulnocarpal ligaments, and interosseous membrane. Nowadays, this method is used to treat ulnar-sided wrist pain, for which we have also started to use a treatment algorithm. The purpose of this study was to review the long-term and clinical results based on our algorithm.Materials and Methods We retrospectively reviewed 30 patients with ulnocarpal impaction syndrome after a minimum follow-up of 5 years (Group A) and then retrospectively evaluated 66 patients with recalcitrant ulnar wrist pain treated based on our algorithm (Group B).Description of Technique Ulnocarpal abutment was confirmed arthroscopically. The distal ulna was approached through a longitudinal incision between the extensor carpi ulnaris and flexor carpi ulnaris. We performed a transverse resection of the ulna fixed with a small locking compression plate. The contralateral side served as the reference for the length of shortening (mean, 2.4 mm; range, 1–5 mm). Disappearance of ulnar abutment was then confirmed again arthroscopically.Results (Group A) Most patients showed good long-term clinical results. About half of the patients showed a bony spur at the distal radioulnar joint (DRUJ), but the clinical results did not significantly correlate with presence of bony spurs. Radiological parameters wre not related to the presence of bony spurs. (Group B) Twenty-four of the 66 patients investigated prospectively underwent an ulnar shortening osteotomy, with all showing good clinical results at 18 months postoperatively.Conclusions Ulnar shortening osteotomy can change the load of the ulnar side of the wrist and appears useful for ulnar-sided wrist pain in the presence of ulnar impaction.Level of evidence IV
Keywords: ulnar shortening osteotomy; ulnar-sided wrist pain; TFCC; DRUJ; arthroscopy